The Effect Of Learning According To Biorhythm Cycles (Mental & Physical) On The Development Of Some Basic Skills In Volleyball For Secondary School Female Students - Ibrahim, Huda; Daham, Lelo (Journal of Physical Education, 2018)
The Effect Of Learning According To Biorhythm Cycles (Mental & Physical) On The Development Of Some Basic Skills In Volleyball For Secondary School Female Students The problem of the research lies in not taking individual differences into consideration during physical education lesson as well as the lack of studies that tackle biorhythmic cycles and their relationship with learning. The importance of the research lies in designing a teaching program based on biorhythmic cycles for learning motor skills. The research aimed at deigning a teaching program for learning underarm pass, receive and serve according to the students’ mental and physical cycles. In addition to that, the researcher aimed at identifying the effect of this teaching program on learning these skills. The researcher hypothesized significant statistical differences between pre and posttests. The researcher used the experimental method. The subjects were (6) students with mental and physical biorhythms close to each other. After the application of the teaching program the researcher concluded that taking biorhythmic cycles into consideration during teaching have a positive effect on learning motor skills and avoiding injuries. Finally she recommended identifying the biorhythm of students before designing teaching programs to avoid fatigue, injuries and for better benefitting from biorhythm in teaching. Keywords: biorhythm, volleyball, fundamental skills.